Filling of electronic states and crystal lattice deformation around dislocation wall - Peleschak, R.M. (Condensed Matter Physics, 2000)
Within the band model we study the electron redistribution around the dislocation wall depending on the conduction band ﬁlling ( 0 < n < 1 ) taking into account the electron-deformation coupling. We show that as the conduction band ﬁlling n increases, the redistribution gets more localized around the dislocation plane. It is established that an increase of the distance between the neighbouring dislocations raises the period of changes in charge density redistribution ∆n along the dislocation wall, whereas a change in the amplitude of the electron redistribution as a function of the distance to the dislocation plane is smoother. У рамках зонної моделі з врахуванням електрон-деформаційного зв’язку досліджено електронний перерозподіл в околі стінки дислокацій в залежності від ступеня заповнення ( 0 < n < 1 ) зон провідності. Показано, що зі збільшенням ступеня заповнення зони провідності n перерозподіл має більш локалізований в околі площини дислокацій характер. Встановлено, що збільшення відстані між сусідніми дислокаціями приводить до збільшення періоду зміни перерозподілу електронної густини ∆n вздовж розміщення стінки дислокацій, а зміна амплітуди електронного перерозподілу як функції відстані до площини дислокацій має при цьому більш плавний характер.